2013
DOI: 10.1097/meg.0b013e32835ab5dc
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen derivatives

Abstract: Sex differences in the incidence of liver cirrhosis and portal hypertension have been reported by epidemiological studies. Previous studies have indicated that estrogen therapy improved hepatic fibrosis, inhibited the activation of hepatic stellate cells, and reduced portal pressure, whereas the administration of exogenous estrogens resulted in some potential risks, limiting their clinical use. However, the biological actions of estrogens are mediated by three subtypes of estrogen receptors (ERs): ERα, ERβ, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 104 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Gender differences in the incidence of liver cirrhosis, PHT, and vascular responsiveness have been demonstrated by some epidemiological and experimental studies[3-6]. Cirrhotic rats treated with estradiol showed a significant decrease in portal pressure and a significant increase in hepatic blood flow, consistent with increased nitric oxide synthase in sinusoidal endothelial cells and inhibited activation of hepatic stellate cells.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Gender differences in the incidence of liver cirrhosis, PHT, and vascular responsiveness have been demonstrated by some epidemiological and experimental studies[3-6]. Cirrhotic rats treated with estradiol showed a significant decrease in portal pressure and a significant increase in hepatic blood flow, consistent with increased nitric oxide synthase in sinusoidal endothelial cells and inhibited activation of hepatic stellate cells.…”
Section: Introductionmentioning
confidence: 86%
“…Cirrhotic rats treated with estradiol showed a significant decrease in portal pressure and a significant increase in hepatic blood flow, consistent with increased nitric oxide synthase in sinusoidal endothelial cells and inhibited activation of hepatic stellate cells. However, ICI-182.780 (an estrogen receptor antagonist) completely inhibits the reduction of portal pressure and elevation of hepatic blood flow[6,7]. Estradiol inhibits the activation of transcription factors by suppressing reactive oxygen species generation and mitogen-activated protein kinase pathways, and inactivates the downstream transcription processes involved in transforming growth factor-β1 expression and hepatic stellate cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…In LSECs, estrogens, even by modulating the levels and the nuclear occupancy of ER (372), enhance the production of nitric oxide (NO) and regulate the hepatic sinusoidal microcirculation (383,384), likely explaining the higher incidence of liver cirrhosis with portal hypertension in men and post-menopausal women than pre-menopausal women (385).…”
Section: Liver Sinusoidal Endothelial Cells (Lsecs)mentioning
confidence: 99%
“…Lastly, and slightly tangentially, PACAP expression in the liver is upregulated after exposure to the xenohormone bisphenol A, which imitates estrogen 55 . Women have a lower incidence of cirrhosis, possibly in part owing to a protective effect of oestrogen against fibrosis, 137 and studies have shown oestrogen derivatives to have antifibrogenic effects and inhibit activation of quiescent HSCs 138 . The topic of oestrogen and PACAP signalling in the CNS has been given some attention, 139 but the interaction between the two outside the CNS remains poorly illuminated.…”
Section: Pacap In the Livermentioning
confidence: 99%